Efficacy, Safety, Pharmacokinetics, and Microbiome Changes of Ibezapolstat in Adults with Clostridioides difficile Infection: A Phase 2a Multicenter Clinical Trial . (4th February 2022) - Garey, Kevin W; McPherson, Jacob; Dinh, An Q; Hu, Chenlin; Jo, Jinhee; Wang, Weiqun; Lancaster, Chris K; Gonzales-Luna, Anne J; Loveall, Caroline; Begum, Khurshida; Jahangir Alam, M; Silverman, Michael H; et al.
Abstract: Background: This study was the first human validation of the gram-positive bacterial DNA polymerase IIIC target in patients with Clostridioides difficile infection. The primary objectives were to assess clinical cure rates and adverse events (AEs). Secondary objectives were to evaluate plasma/fecal pharmacokinetics, microbiologic eradication, microbiome and bile acid effects, and sustained clinical cure (SCC) with ibezapolstat. Methods: This single-arm, open-label, phase 2a study enrolled adults with C. difficile infection at 4 US centers. Patients received ibezapolstat 450 mg orally every 12 hours for 10 days and followed for an additional 28 days to assess study objectives. Results: Ten patients with a mean (standard deviation [SD]) age of 49 [15] years were enrolled. Seven AEs were reported classified as mild-moderate. Plasma levels of ibezapolstat ranged from 233 to 578 ng/mL while mean (SD) fecal levels were 416 (494) µg/g stool by treatment day 3 and >1000 µg/g stool by days 8–10. A rapid increase in alpha diversity in the fecal microbiome was noted after starting ibezapolstat therapy, which was maintained after completion of therapy. A proportional decrease in Bacteroidetes phylum was observed (mean change [SD], −10.0% [4.8%]; P = .04) with a concomitantly increased proportion of Firmicutes phylum (+14.7% [5.4%]; P = .009). Compared with baseline, total primary bile acids decreased by a mean (SD) of 40.1 (9.6) ng/mg stool during therapy ( P < .001) and 40.5 (14.1) ng/mg stool after completion of therapy ( P = .007). Rates of both initial clinical cure and SCC at 28 days were 100% (10 of 10 patients). Conclusions: In this phase 2a study, 10 of 10 patients achieved SCC, demonstrated favorable pharmacokinetics, minimal AEs, and beneficial microbiome and bile acids results. These results support continued clinical development. Abstract : This single-arm, phase 2a study was the first validation of ibezapolstat in adult patients with Clostridioides difficile infection. Ten of 10 patients achieved sustained clinical cure and demonstrated favorable pharmacokinetics, minimal adverse events, and beneficial microbiome and bile acids results.